Effects of high-molecular-weight glutenin subunit on hard-steamed bread quality - Zhao, Jing; Wang, Tianyi; Zhao, Jiajia; Qiao, Ling; Wu, Bangbang; Hao, Yuqiong; Ge, Chuan; Feng, Zhiwei; Zheng, Xingwei (Frontiers in Genetics, 2024)
Steamed bread (SB) is a daily food in many countries in the world, but the relationship between HMW-GS and the quality of SB remain unclear. This study investigated the effects of 12 subunit combinations on the characteristics of SB, including volume, physical properties, and sensory evaluation, combined with the microstructure and dough rheological properties. The locus effect results showed, volume and physical properties of SB were Glu-D1>Glu-B1>Glu-A1, while sensory scores Glu-B1>Glu-D1>Glu-A1. According to individual subunit effects, subunit 1 at Glu-A1 locus, 7+8and 7+9 subunits at Glu-B1 locus, and 2+10 and 5+12 subunits at Glu-D1 locus were significantly superior to other subunits in physical indices like volume, chewiness, glueyness, and sensory scores, and were less affected by moisture. The effect of subunits combination is mainly affected by subunits, and the combination of superior subunits tends to make SB quality better. The subunit combinations (1,7+8,5+12), (N,7+9,2+10) and (1,7+9,5+12) had better physical properties indexes, sensory scores, dense, uniform and delicate micro-pore structure, and smaller thickness wall. The results showed that protein content, wet gluten content and stability time were the main factors affecting the volume and physical properties of SB. The protein content, wet gluten content and stability time of flour in 7+8, 7+9, 2+10 and 5+12 subunits were higher. Therefore, the quality of SB containing these subunits was found better.